Chandrasekhar and his limit - Venkataraman, G. (Hyderabad, Universities Press (India)Limited, 1992)
It is a heartwarming and very inspiring story about Subrahmanyam Chandrasekhar, the most distinguished mathematical physicist India has produced. In a long and remarkable career, Chandrasekhar has done many outstanding things but this book concentrates mostly on one of them, namely, the discovery of the Chandrasekhar Limit.
Index 137-139p.
Keywords: Physics